2022
DOI: 10.1007/s12012-022-09729-7
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H2S Ameliorates High Salt-Induced Hypertension by Alleviating Oxidative Stress and Inflammation in the Paraventricular Nucleus in Dahl S Rats

Abstract: Hydrogen sulfide (H2S) is an important gaseous signaling molecule that regulates cardiovascular activity in animals. The hypothalamic paraventricular nucleus (PVN) is a major integrative region involved in blood pressure (BP) regulation. We explored whether exogenous H2S application by intraperitoneal injection of sodium hydrosulfide (NaHS) alleviates BP increase induced by a high salt diet (HSD) and the role of PVN in Dahl salt-sensitive (Dahl S) rats. Dahl S rats were divided into four groups according to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Researchers have also found that NF-κB activities in the PVN are closely associated with the intensity of SNA in hypertensive rats [ 24 , 47 ]. NF-κB and oxidative stress in PVN play crucial roles in the pathogenesis of hypertension [ 38 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also found that NF-κB activities in the PVN are closely associated with the intensity of SNA in hypertensive rats [ 24 , 47 ]. NF-κB and oxidative stress in PVN play crucial roles in the pathogenesis of hypertension [ 38 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of NF-κB in the PVN is closely related to the enhancement of SNA. Inhibiting NF-κB activities greatly reduced ROS and SNA in hypertension [ 24 ] and myocardial infarction rat models [ 25 , 26 ]. The authors of [ 27 ] found that NF-κB activity increased in myeloid-specific SIRT1 knockout mice, suggesting that SIRT1 in bone marrow may inhibit NF-κB activation.…”
Section: Introductionmentioning
confidence: 99%
“…This study used HE staining to observe the effects of long-term high salt diet on the structure of the heart and arteries in rats. The process of HE staining was performed as previously described ( Liao et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, chronic neuroinflammation in the paraventricular nucleus of the hypothalamus induced by long-term high salt intake could lead to HTN in the Dahl salt-sensitive rat model. 118 , 119 On another side, HTN could also induce microvascular inflammation in the brain. So, cerebral microvascular inflammation likely accelerated cognitive impairment in the elderly with AD under HTN.…”
Section: Pathogenesis Of Hypertension and Alzheimer’s Disease: Experi...mentioning
confidence: 99%